Phytoextraction Potential of Colocasia esculenta for Cadmium- and Zinc-contaminated Soils under Moderate Drought Stress: A Short-Term Pot Study - Saeng-ngam, Sukhumaporn; Larpkern, Panadda; Moungsrimuangdee, Boontida; Jampasri, Kongkeat (Journal of Current Science and Technology, 2026)
This study investigates the effects of moderate drought on growth, physiology, and heavy metal accumulation in Colocasia esculenta cultivated in cadmium (Cd) and zinc (Zn) contaminated soils. Plants were grown for 30 days under moisture levels of 100% (well-watered), 60%, and 40% field capacity (FC), representing moderate drought, in soils containing 100 mg/kg Cd and Zn. Drought had no impact on the relative growth rate (RGR), whereas metal exposure significantly reduced dry weight and stem height (p < 0.05) of the plants. The photochemical efficiency of PSII (Fv/Fm) and chlorophyll content remained stable (p > 0.05), but the water content (WC) of the leaves decreased under drought stress (p < 0.05). Translocation factors (TF) for both metals were above 1 in all treatments, indicating that heavy metal predominantly accumulated in shoots, with Cd exhibiting greater bioaccumulation factors (BAF) (2.40–3.03) than Zn (1.39–2.98). Overall, moderate drought limited biomass production but enhanced the accumulation of Cd and Zn and translocation to the shoots. These findings suggest that C. esculenta is suitable for the phytoextraction of Cd- and Zn-contaminated soils under drought-stress conditions after short-term exposure of 30 days. However, reduced biomass under drought may decrease overall phytoextraction despite higher tissue concentrations. Therefore, field-scale investigations under variable rainfall conditions are still required.